An Impulse Dynamic Model for Computer Worms - Chunming Zhang; Yun Zhao; Yingjiang Wu (Abstract and Applied Analysis)
A worm spread model concerning impulsive control strategy is proposed and analyzed. We prove that there exists a globally attractive virus-free periodic solution when the vaccination rate is larger than θ1. Moreover, we show that the system is uniformly persistent if the vaccination rate is less than θ1. Some numerical simulations are also given to illustrate our main results.